Grip strength in youth ice hockey players: Normative values and predictors of performance - Toong, T.; Wilson, K. E.; Urban, K.; Paniccia, M.; Hunt, A. W.; Keightley, M.; Reed, N. (The Journal of Strength and Conditioning Research, 2018)
Grip strength is a simple, valid, and reliable tool for estimating overall muscular strength, a key component of health-related fitness and sport performance. To date, there is a paucity of up-to-date and developmentally sensitive grip strength norms specific to youth-athlete populations. The objectives of this study are to (a) establish normative grip strength values in youth ice hockey players, (b) descriptively compare these values with existing Canadian pediatric norms, and (c) explore the relationship between age, sex, body mass, and hockey playing level on grip strength performance. A sample of 690 male and female youth ice hockey players between the ages of 10 and 16 years were included. Participants completed assessments of maximal grip strength using a hand dynamometer on both hands. In addition, age, sex, body mass, and hockey playing level were collected. Maximal absolute grip strength, stratified by age and sex, was higher than previously published Canadian pediatric norms. Grip strength increased with age in both sexes. Males and females performed similarly until 12 years of age, after which point males had greater strength. Individuals with greater body mass had greater strength. For the nondominant hand, competitive players had greater strength than those playing house league or select. This study describes normative grip strength values in youth ice hockey players according to age, sex, body mass, and playing level. These athlete-specific norms may be used to help evaluate and monitor changes in grip strength over time in youth ice hockey players.